中國土地所有權의 法律制度에 대한 考察 - 趙東濟(Cho Dong-Je) (Tonga pŏphak, 2009)
With the development of social economy, land ownership system of china demonstrates many drawbacks. Nominal subject of land ownership is the deep-seated reason land problems in China now. The difference that owned by public system in land with private legal theory makes the property law of China meet an unprecedented challenge, the national and holding power gathers the civil corpus and the administration corpus as one, the easy to government make use of behavior to carry on an aggressive intervention to the land with insure the exploitation of land can be kept on, but it is possible that the influence of exorbitant intervention make less efficiency of land exploitation, intervention of the form mainly should be the strict performance the plans of land. Such as the subject of collective ownership of land nominal to put, the object of the right of ownership boundary line unclear landing to a lot of land is barren and interests of peasants damaged. Through the description and analysis of the historical changes of Chinese rural land property rights system, can clearly see an important influence of the Chinese rural land property system in the process of reform and opening-up as well as its important role. KCI Citation Count: 16